Challenges and gender differences in implementing gamification approach among vocational college lecturers in Malaysia. - Omar, Marlissa (Areadiscover, 2023)
Background and Purpose: Gamification is a teaching and learning approach that is gaining popularity among teachers as a way to make classroom learning more enjoyable and engaging with the use of rewards to celebrate accomplishments. With the rise of online learning in Malaysian educational institutions, gamification is viewed as an interactive method of teaching and learning. Due to the fact that limited studies have been conducted to investigate the challenges in implementing gamification approaches among vocational instructors, it is the aim of this paper; therefore, to examine the challenges. Methodology: This study employed a quantitative research method. The respondents include 55 vocational lecturers from several vocational colleges in Malaysia. A set of questionnaires was used to examine the challenges faced by the lecturers in the implementation of gamification at their institutions. Four constructs were used to differentiate the differences of the challenges, which include support, access, competency, and applicability. Data collected from this study were analyzed using descriptive statistics (mean score and standard deviation) and inferential statistics (independent sample t-test) to identify the differences between gender. Findings: The findings of this study indicated that the majority of vocational lecturers have moderate challenges when implementing gamification approaches in their teaching and learning based on the findings related to the constructs. In addition, it was found that there were no significant gender differences in terms of the difficulties associated with implementing gamification approaches. This study also showed that most vocational lecturers have the potential to apply gamification in their teaching based on their high competencies with adequate support and enough access given to them. Contributions: The findings of the study can contribute to vocational lecturers to promote gamification approach during the learning process to increase students’ motivation.